2010
DOI: 10.1007/s00192-010-1257-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue response to a new type of biomaterial implanted subcutaneously in rats

Abstract: The MPEG-PLGA is highly biocompatible, degrades quickly, and seems inert in the process of tissue regeneration. Thus, it is hardly a candidate per se in reinforcement of pelvic reconstruction, but it could have a future role as carrier for stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…By using an abdominal wall defect model in rats, we confirmed our previous findings [11] that the MPEG-PLGA scaffold is very biocompatible and disappears completely in 8 weeks. Desmin-positive muscle cells that were separated from the ordinary muscle layers of the abdominal wall were observed, and fluorescence-positive cells could be traced after 8 weeks, indicating survival and proliferation of cells originating from the MFF.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By using an abdominal wall defect model in rats, we confirmed our previous findings [11] that the MPEG-PLGA scaffold is very biocompatible and disappears completely in 8 weeks. Desmin-positive muscle cells that were separated from the ordinary muscle layers of the abdominal wall were observed, and fluorescence-positive cells could be traced after 8 weeks, indicating survival and proliferation of cells originating from the MFF.…”
Section: Discussionsupporting
confidence: 75%
“…The MPEG-PLGA scaffold is a freeze-dried combination of glycolic acid and lactic acid, which makes the structure porous and spongy as previously described [11].…”
Section: Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 At 3 weeks postimplantation, inflammatory scores were qualitatively assessed as 3 or moderate and by 8 weeks had decreased to 1 or minimal. 10,33 However, our inflammatory response was more similar to the acellular skeletal muscle scaffolds implanted into the skeletal muscle of mice reported by Perniconi et al They found that there was an overt inflammatory response 2 weeks postimplantation, but by 4 weeks it had decreased toward control levels. 9 Longer studies are necessary to determine whether the inflammation caused by the implantation of the scaffold continues to decrease over time.…”
Section: Discussionsupporting
confidence: 79%
“…Apart from the fact that different parts of the meshes are studied for histology making comparisons difficult [26, 27] more relevant is the problem of subjectivity during the scoring process. In the current study, a software detected the positive staining on each section on the same set of mesh filaments and calculated the percentage stained area.…”
Section: Discussionmentioning
confidence: 99%